Explaining the Role of Motivation in Opposition to Nuclear Power Energy - Focusing on EIV (Expectancy, Instrumentality, and Valence) in Expectancy Theory - 김미리; 김서용 (Crisisonomy, 2018)
In the age of information society, the internet is full of useful information which individuals can utilize for their critical decision making, such as the judgment on nuclear power energy. Based on the internet information, individuals can take actions for or against nuclear power energy. In this process, motivation plays a critical role in taking counteraction against nuclear power energy. Based on the survey data collected from 1,572 internet users in Korea, this study examines the impacts of the information-related motivation factors on opposition action online. We applied the Victor Vroom’s expectancy theory that used EIV (Expectancy, Instrumentality and Valence) as main motivation factors. We compared the explanatory power of EIV with that of psychometric paradigm as a direct explanatory variable, and analyzed the role of EIV as a moderator.
Keywords: Vroom’s expectancy theory; EIV(Expectancy; Instrumentality and Valence); opposition action to nuclear power energy